A Glimpse at Ethiopian Universities from Globalisaton Perspectives: Institutional Policy Responsiveness for Local and Global Realities - Olkaba, Teklu Tafase; Edosa, Kitessa Chemeda (Advances in Social Sciences Research Journal, 2017)
The impact of globalisation on higher education institution policies and government development policies are emerging issues among researchers and policy makers.The study explored a range of literature on globalization policy and its impact on higher education operations. Based on the literature review, the empirical study examined realities of understanding in Ethiopian higher education and its institutional policy responsiveness to the current local and global knowledge economy. The study was framed with the research question:To what extent have universities in Ethiopia embraced the reality of globalisation? Six experienced Ethiopian universities were purposively selected for the study. From these universities 289 postgraduate students and 256 senior staff from the ranks of lecturer, assistant professor and associate professor were involved in the study. The findings of the study conclude that in the global knowledge economy, the role of Ethiopian universities requires a change in policies and practices and systems, with respect to local and global contexts towards the creation of a distinctly new global model of higher education.